Physiological quality of Brachiaria brizantha seeds - Augusto do Lago, Antonio; Martins, Leila (Pesquisa Agropecuaria Brasileira, 1998)
The available information concerning an adequate evaluation of the physiological quality of forage grasses seeds of tropical and subtropical distribution, such as those of the Brachiaria genus are still insufficient. Aiming to study the efficiency of several methods for determining the physiological quality and for reducing dormancy of B. brizantha seeds, ten commercial seed lots of the Marandu cultivar, from the 92/93 crop year, were, at four months after harvest, evaluated in relation to germination (just 0.2% KNO3 in the substrate), germination after preheating at 40oC for seven days, accelerated aging at 42oC for 60 hours, and modified cold test at 10oC for seven days. These evaluations were carried out with and without scarification with concentrated sulphuric acid for 15 minutes, and the countings were made at 7, 14 and 21 days after seeding. Results showed that acid scarification, preheating, accelerated aging and exposition to cold produced, isolatedly, favorable effects in breaking seed dormancy. Acid scarification after preheating and before exposition to cold increased germination but reduced it when applied just after the artificial aging. The most effective process for obtaining highest germination was preheating at 40oC for seven days followed by scarification with concentrated sulphuric acid for 15 minutes.